Size at sexual maturity in Cardisoma crassum (Brachyura: Gecarcinidae) from the Gulf of Montijo, Panama - Lombardo González, Roberto C. (2025)
The morphometric and physiological maturity sizes of the mouthless crab Cardisoma crassum in the Gulf of Montijo, Panama, were studied from August 2023 to August 2024. The L50 parameter for the male morphometric estimate ranged from 54.80 to 63.70 mm carapace width. In contrast, the L50 estimation based on male gonadal stages was 52.70 mm. For females, the L50 morphometric estimate ranged from 49.60 to 56.00 mm carapace width, while the L50 based on the female gonadal stage assessment was 51.50 mm. Gravid females were recorded from July to September, suggesting a reproductive peak during the rainy season. The maturation cycle appears to extend from January to April, followed by peak incubation in July and September. Size variation across sampling sites suggests differences in habitat quality; however, fishing pressure may also shape population structure, as average crab carapace was smaller compared to previous studies in the same region. A minimum landing size of 58 to 60 mm carapace width is recommended to support fishery management in the future.